Ongoing population decline and range contraction in Norwegian forest grouse - Gregersen, Finn; Gregersen, Håkon (Ornis Norvegica, 2009)
Forest grouse diverge in niche, where Capercaillie Tetrao urogallus thrives in older forests, Hazelgrouse Bonasa bonasia is a habitatspecialist (middle-aged decidous-rich coniferous forest) and Black Grouse T. tetrix is an early succesionalist. We analysed the hunting statistics over four decades in Norway to explore divergence among forest grouse in spatio-temporal trends and discuss these findings in relation to factors changing habitats for these species. Overall, modern forestry has continuously modified the forests, especially Hazelgrouse and Capercaillie habitats. In the same time, climate has become warmer and more humid pushing climate zones northwards. In this study, all species revealed declines compared to the 1970s, especially profound into south and in the northernmost county. This response was strongest for Hazelgrouse and next Capercaillie. Central, inland counties along the Swedish border reveal smaller declines and are probably source areas. We propose that the effect of climate and forestry interact to reduce habitat optimality for forest grouse, and that these effects are stronger in sinks, potentially initiating range-contraction.